Potential of Algae–Bacteria Synergistic Effects on Vegetable Production - Kang, Yeeun; Kim, Minjeong; Shim, Changki; Bae, Suyea; Jang, Seonghoe (Frontiers in Plant Science, 2021)
Modern agriculture has become heavily dependent on chemical fertilizers, which have caused the environmental pollution, the loss of soil fertility and sustainability. Microalgae and plant growth promoting bacteria (PGPB) have been identified as an alternative to chemical fertilizers for improving soil fertility due to their biofertilizing properties through the production of bioactive compounds (e.g., phytohormones, amino acids, carotenoid, etc.) as well as inhibitory activities against plant pathogens. Although single species-based treatment of microalgae or bacteria has been commonly used in agriculture, growing experimental evidences suggest that microalgae and bacteria in the symbiotic relationship synergistically affect each other’s physiological and metabolomic processes. Moreover, the co-culture/combination of microalgae with bacteria is considered as a promising approach in biotechnology for wastewater treatment and efficient biomass production based on the advantage of the synergistic effect. However, much remains to be explored on the microalgal-bacterial interaction for agricultural application. In this review, we summarize the effects of microalgae and PGPB as biofertilizer agents on vegetable cultivation and, furthermore, present the potential of the microalgae-PGPB co-culture system for environmentally compatible production of vegetables with better quality.